Cabo Verde : Staff Report for the 2019 Article IV Consultation and Request for an Eighteen-Month Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Cabo Verde. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Cabo Verde's 2019 Article IV Consultation and Request for an Eighteen-Month Policy Coordination Instrument (PCI). The PCI aims at bolstering macroeconomic stability through fiscal consolidation and growth-enhancing reforms to support medium-term fiscal and debt sustainability. Policy discussions and the PCI-supported program focused on achieving medium-term fiscal and debt sustainability; modernizing the monetary policy framework and continuing to build precautionary reserves; bolstering the financial system resilience; restructuring lossmaking State-Owned Enterprises; and advancing structural reforms to support private sector-led growth. The medium-term outlook is positive although risks are tilted to the downside. Economic growth is projected to remain robust while the fiscal and external positions are expected to improve further, underpinned by growth and programmed structural reforms.